Egg consumption and growth in children: a meta-analysis of interventional trials - Larson, Elisabeth A.; Zhao, Zaixin; Bader-Larsen, Karlen S.; Magkos, Faidon (Frontiers in Nutrition, 2024)
Introduction Stunting and wasting are prevalent in low- and middle-income countries, putting children at risk for disease and disability. Eggs are a nutrient-rich food that can potentially facilitate growth. Purpose The aim of this meta-analysis was to evaluate the potential beneficial effect of egg supplementation on growth in children. Methods Following the PRISMA guidelines, PubMed and Healthline (Ovid) were systematically searched for interventional studies on egg supplementation for growth in children aged 6 months to 18 years, with no restrictions on date. Studies were evaluated for quality using Cochrane’s GRADE technique. Data were pooled and reported as means and 95% confidence intervals. Results Seven studies reporting on 9 unique interventions in 3,575 male and female participants were included in the meta-analysis. Participants in the intervention groups experienced significantly greater increases in height/length (by 0.47 [0.13, 0.80] cm, p < 0.01) and weight (by 0.07 [0.01, 0.13] kg, p = 0.03) when compared to those in the control groups. Conclusion Eggs are an affordable, nutritious option for improving growth in children, though more studies with longer interventions are warranted. Systematic review registration: PROSPERO (CRD42021289609: https://www.crd.york.ac.uk/prospero/).